Egyptian-Iraqi relations 1936-1922 Historical research - Hamid, Dr.Mohammed Abbas; Hamid, Dr.Mohammed Abbas (Sulaimani Journal for Humanities, 2026)
Egyptian-Iraqi relations 1922-1936 are considered to be important Arab relations, because after the fall of the Ottoman Empire, although both Egypt and Iraq were under British rule, but both countries gained their independence Egypt came to power in 1922 under the leadership of Fuad I. During this period, political and cultural cooperation between the two countries began Diplomatic relations, especially the opening of consulates between Egypt and Iraq, were established during this period. For this purpose, several questions have been raised, such as what impact did British policy in both Egypt and Iraq have on foreign relations in both countries? What was the reflection of the 1927 British-Iraqi Treaty in Egypt? How did Egyptian public opinion respond to the 1930 Iraqi-British treaty? What was Egypt's attitude towards Iraq's accession to the League of Nations in 1932? . . . .
Keywords: Egypt; Iraq; British; agreement and consulate